2019
DOI: 10.3390/ma12182993
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Characterization of 3D Printed Cementitious Materials

Abstract: Three-dimensional concrete printing (3DCP) has progressed rapidly in recent years. With the aim to realize both buildings and civil works without using any molding, not only has the need for reliable mechanical properties of printed concrete grown, but also the need for more durable and environmentally friendly materials. As a consequence of super positioning cementitious layers, voids are created which can negatively affect durability. This paper presents the results of an experimental study on the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(80 citation statements)
references
References 27 publications
3
57
1
1
Order By: Relevance
“…Roussel [13] showed that the bond strength could differ by even up to 50% when drying was occurring in the printed layers. Following this, studies have shown that the bond strength is dependent on the moisture content at the layer interface [120,121]. In summary, the bond strength is influenced not only by the mixture properties but also by the print parameters such as the time gap between the deposition of layers and the ambient atmospheric conditions such as temperature, relative humidity, wind velocity during printing.…”
Section: Materials Behaviour In the Hardened Statementioning
confidence: 92%
“…Roussel [13] showed that the bond strength could differ by even up to 50% when drying was occurring in the printed layers. Following this, studies have shown that the bond strength is dependent on the moisture content at the layer interface [120,121]. In summary, the bond strength is influenced not only by the mixture properties but also by the print parameters such as the time gap between the deposition of layers and the ambient atmospheric conditions such as temperature, relative humidity, wind velocity during printing.…”
Section: Materials Behaviour In the Hardened Statementioning
confidence: 92%
“…It can be noted that the bending resistance was significantly lower for this direction on loading due to the anisotropic behavior of the printed structure. This anisotropic behavior was due to the very high yield stress value of the printed cementitious materials, which led to an imperfect interface between layers [31].…”
Section: Bending Resistancementioning
confidence: 99%
“…Bos et al also studied the effect of a steel wire embedded in the deposited layer as a potential efficient reinforcement strategy [29]. However, those two previous methods did not provide reinforcement that crossed the interface between layers that were expected to be a potential weakness zone of the printed structures [11,[30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the transmission of flexural loads can be enhanced and the effect of cold joints, as described e.g., in [5,6], reduced. As described in Section 1.2, the layer bond often represents a weakness zone in extrusion [22,23]. This is especially true for the production of larger building elements or the manufacturing of houses at side, where the time gap between layers increases and additionally, a need to pause the printing process might occur.…”
Section: Overarching Discussionmentioning
confidence: 99%
“…Thus, the strength of the layer bonding may either be not affected or even be deteriorated due to increased anisotropy. The layer bond was therefore identified as the weakest zone of the elements [22,23].…”
Section: Reinforcement Systems For Extrusion (State Of the Art)mentioning
confidence: 99%